2021
DOI: 10.3390/en14102921
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Substrate on the Optic Performance of Retro-Reflective Coatings: An In-Lab Investigation

Abstract: Retro-reflectivity is a promising surface capability, which has attracted the interest of researchers for building applications in order to counteract Urban Heat Island (UHI) effects. This work aims at studying the impact of the substrate material on the optic performance of retro-reflective (RR) coatings. Three types of substrate materials were investigated: smooth pine wood panels, rough plywood panels, and smooth acetate sheets. The RR coating samples were made by firstly adding a high reflective white pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Results from this previous contribution [10] showed that the glass beads modified the global reflectance of the high-reflective paint, but they provided a directional reflectance capability to the coating. It was demonstrated that the HR coating exhibited the highest global reflectance (80.1%), whereas for the RR coating it decreases to 72.8% [10]. Despite this lower global reflectance, the RR coating provides a strong retro-reflective component for incident directions near the normal to the surface (i.e.…”
Section: High-reflective and Retro-reflective Coatingsmentioning
confidence: 97%
See 4 more Smart Citations
“…Results from this previous contribution [10] showed that the glass beads modified the global reflectance of the high-reflective paint, but they provided a directional reflectance capability to the coating. It was demonstrated that the HR coating exhibited the highest global reflectance (80.1%), whereas for the RR coating it decreases to 72.8% [10]. Despite this lower global reflectance, the RR coating provides a strong retro-reflective component for incident directions near the normal to the surface (i.e.…”
Section: High-reflective and Retro-reflective Coatingsmentioning
confidence: 97%
“…the ratio between glass beads and white paint was 1:1). In a previous work [10], the optical performance of the abovementioned HR and RR coatings was analyzed in lab with both spectrophotometric and angular reflectivity characterization. Results from this previous contribution [10] showed that the glass beads modified the global reflectance of the high-reflective paint, but they provided a directional reflectance capability to the coating.…”
Section: High-reflective and Retro-reflective Coatingsmentioning
confidence: 99%
See 3 more Smart Citations